Calculation and Analysis of Time Varying Mesh Stiffness of Gear with Considering Translational Freedom - Te Chen; Huaguo Chen; Jianmin Li; Hang Yu (Jixie chuandong)
During the gears meshing process, the Time Varying Meshing Stiffness (TVMS) is affected by the relative displacement. An algorithm of TVMS considering two translational degrees of freedom is proposed. The algorithm is based on the potential energy method for the ideal involute spur gear. The translational freedom is introduced into the calculation of TVMS by considering the influence of translational freedom on the angles in gear meshing. The effect of gears relative displacement on the maximum, mean and contact ratio of TVMS is studied. The results show that TVMS is most sensitive to the relative translation of gears along the vertical direction of the meshing line, and is least sensitive to the relative translation of gears along the direction of the meshing line. In the vertical direction of the meshing line, the 0.1 mm relatively movement can cause 0.93% change of the mean of TVMS.